Sorafenib modulates the gene expression of multi-drug resistance mediating ATP-binding cassette proteins in experimental hepatocellular carcinoma - Hoffmann, Katrin; Franz, Clemens; Xiao, Zhi; Mohr, Elvira; Serba, Susanne; Büchler, Markus W.; Schemmer, Peter (Anticancer research, 2010)
Background: High ATP-binding cassette (ABC) protein expression leads to intrinsic drug resistance of hepatocellular carcinoma (HCC). The aim of this study was to investigate the potential chemosensitizing effects of sorafenib on the multi-drug resistance (MDR) phenotype. Material and Methods: The ABC-protein gene expression and the cellular survival were determined by RT-PCR analysis and MTT assay in HUH7 cells. Results: Sorafenib inhibits MDR. The ABC-protein mRNA expression decreased by up to 51% (p≤0.01). Addition of sorafenib to conventional chemotherapy restored the chemosensitivity. Combination of gemcitabine plus sorafenib decreased the ABC-protein mRNA levels by up to 77%, compared to gemcitabine monotherapy (p≤0.001). Doxorubicin plus sorafenib decreased the ABC-protein mRNA levels up to 74% compared to doxorubicin monotherapy (p≤0.001). Conclusion: This study provides evidence that the MDR phenotype of HCC cells can be modulated by the multi-kinase inhibitor sorafenib and consequentially may lead towards personalized therapies in patients with highly resistant tumors.
Gesehen am 13.03.2023